Long distance data transfer using spatial modes of light - Gailele, Lucas Mushimanekgapi (My University, 2018)
Free space optical communication has been the subject of interest recently and has been identiﬁed as an alternative to ﬁbre communication. Communication using the spatial modes of light is the focus of this dissertation. While propagating in free space, spatial modes are able to carry orbital angular momentum (OAM). OAM carrying spatial modes are orthogonal throughout their propagation and they span the discrete inﬁnite dimensional Hilbert space allowing for (in theory) inﬁnite information transfer to be carried throughout propagation. We are particularly interested in Laguerre-Gaussian (LG) modes and the azimuthal (Vortex) modes to send information. We discuss the principle of generating and detecting spatial modes by tailoring the dynamic phase of the spatial mode of light using a spatial light modulator (SLM). We will also characterized the communication link by giving a detailed overview of optical turbulence and how we measure the optical turbulence parameter. We will also give a link budget calculation describing the performance of the communication system.
A dissertation submitted in partial fulﬁlment of the requirements for the degree of Master of Science in the Faculty of Science School of Physics, 2018
Keywords: Angular momentum; Operator theory; Quantum optics